Traditional Elites in the Shadow of Colonialism: The Transformation of the Role of Madurese Nobles in the Dutch East Indies Bureaucracy, 1830–1942 - Maulana Fariqi Nuri; Ari Sapto; Daya Negri Wijaya; Aditya Nugroho Widiadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study analyzes the transformation of the role of Madurese noble elites within the colonial power structure of the Dutch East Indies during the 1830–1942 period. In the pre-colonial era, Madurese nobles possessed absolute sovereignty rooted in feudal legitimacy, lineage, and patronage systems. However, colonial policies through the indirect rule system gradually integrated them into the administrative bureaucracy as mediators between the Dutch government and the local population. The research method employed is the historical method, encompassing heuristics, source criticism, interpretation, and historiography. The results indicate that this transformation caused a shift in legitimacy from traditional-genealogical to rational-bureaucratic, where local elites functioned as tax collection apparatus and social supervisors. Despite being in a subordinate position, the Madurese elites demonstrated agency through policy negotiation and adaptation to modern education as part of bureaucratic professionalization. This study concludes that colonialism in Madura operated effectively by utilizing and modifying deeply rooted traditional social structures.